Optogenetic control of transgene expression in Marchantia polymorpha - Anya Lillemor Lindström Battle; Lee James Sweetlove (Applications in Plant Sciences)
Abstract Premise The model liverwort Marchantia polymorpha is an emerging testbed species for plant metabolic engineering but lacks well‐characterized inducible promoters, which are necessary to minimize biochemical and physiological disruption when over‐accumulating target products. Here, we demonstrate the functionality of the light‐inducible plant‐usable light‐switch elements (PULSE) optogenetic system in Marchantia and exemplify its use through the light‐inducible overproduction of the bioplastic poly‐3‐hydroxybutyrate (PHB). Methods The PULSE system was used to drive expression of luciferase as a reporter and characterize its induction in transgenic M. polymorpha. Additionally, PULSE was used to drive expression of the PHB biosynthetic pathway; the accumulation of PHB under light‐inducible control was compared to constitutive overexpression. Results PULSE was fully functional and minimally leaky in M. polymorpha. The presence of the PULSE construct, even in the absence of induction, resulted in a developmental phenotype. Constitutive and inducible expression resulted in similar PHB accumulation levels. Discussion PHB biosynthesis in plants is known to adversely affect plant health, but placing its production under optogenetic control alleviated negative effects on biomass accumulation in some instances. The work presented here represents a significant expansion of the toolbox for the metabolic engineering of M. polymorpha.